2017
DOI: 10.31018/jans.v9i3.1430
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic variability among different genotypes of Cape gooseberry (Physalis peruviana L.) in India

Abstract: The field experiment was carried out at the research farm of Horticulture Garden, Bihar Agricultural College, Sabour, Bhagalpur during 2014-15 for assessment of genetic variability among different genotypes of cape gooseberry in India. The experiment was laid out in Randomized Block Design with three replications having twelve genotypes. Analysis of variance revealed significant differences among genotypes for all the traits studies which suggesting sufficient variability for yield and quality parameters. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
2
0
1
Order By: Relevance
“…We found broad-sense heritabilities 0.53 and 0.41 for PH and TSS, respectively (Table 1). Kumar et al (2017) found a similar heritability for PH (0.51) in P. peruviana, and Leiva-Brondo et al ( 2001) found heritabilities of 0.53 and 0.87 for TSS in P. peruviana evaluated in glasshouse and outdoors, respectively. The heritability coe cients are measures that vary depending on the genetic variability in the genotypes, the environment conditions and the nature of the trait.…”
Section: Genetic Variation and Parametersmentioning
confidence: 73%
See 1 more Smart Citation
“…We found broad-sense heritabilities 0.53 and 0.41 for PH and TSS, respectively (Table 1). Kumar et al (2017) found a similar heritability for PH (0.51) in P. peruviana, and Leiva-Brondo et al ( 2001) found heritabilities of 0.53 and 0.87 for TSS in P. peruviana evaluated in glasshouse and outdoors, respectively. The heritability coe cients are measures that vary depending on the genetic variability in the genotypes, the environment conditions and the nature of the trait.…”
Section: Genetic Variation and Parametersmentioning
confidence: 73%
“…High genetic variation for yield traits have been found in P. peruviana (Herrera et al 2011;Kumar et al 2017), indicating a potential to produce more than 15 t.ha -1 (Herrera et al 2011) . Using the maximum value of WFP found in our studies, we found that some plots reached potential yields of 16 t.ha -1 of fruits, with the hybrid Can x Laj reaching 9.3 t.ha -1 , on average, reinforcing the potential of P. angulata to be a Brazilian crop.…”
Section: Genetic Variation and Parametersmentioning
confidence: 99%
“…Nilai KVG dan KVF yang sama-sama tinggi merupakan indikator adanya variabilitas yang cukup besar pada karakter tersebut. Hal tersebut sesuai dengan pendapatKumar et al, (2017) bahwa karakter dengan nilai KVG dan KVF yang tidak berbeda secara signifikan menunjukkan bahwa karakter tersebut tidak mendapat pengaruh yang kuat oleh faktor lingkungan. Kegiatan seleksi akan lebih efektif karena variasi diantara genotipe sebagian besar dikendalikan oleh faktor genetik.Tabel 4.…”
unclassified